Constitutionalism and administrative state - the requirements of constitutionalism in the era of the executive supremacy - Arsen Bačić; Petar Bačić (Zbornik Radova Pravnog Fakulteta u Splitu, 2016)
Politics limited by law that subjects every public activity to court or other controls is the basic characteristic and demand of constitutionalism and the rule of law. It is in keeping with the rule of law principle and legitimate constitutional and democratic demands for its supremacy. The state, mostly its executive and other institutions of the system of rule should be subject to the law and various controls. In this text the authors analyse the comparative experience of an administrative state which in almost 100 years of its existence in various ways has put democratic means of control to the test.